2019
DOI: 10.1186/s13054-019-2407-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps (NETs) exacerbate severity of infant sepsis

Abstract: Background Neutrophil extracellular traps (NETs) are innate defense mechanisms that are also implicated in the pathogenesis of organ dysfunction. However, the role of NETs in pediatric sepsis is unknown. Methods Infant (2 weeks old) and adult (6 weeks old) mice were submitted to sepsis by intraperitoneal (i.p.) injection of bacteria suspension or lipopolysaccharide (LPS). Neutrophil infiltration, bacteremia, organ injury, and concentrations of cytokine, NETs, and DNase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 73 publications
7
105
1
4
Order By: Relevance
“…Excessive activation of neutrophils is known to decrease survival and enhance susceptibility to subsequent bacterial infections ( 41 ). One mechanism that may contribute to the pathology of sepsis is the release of neutrophil extracellular traps as they contain the beneficial antimicrobial nuclear proteins but also damaging citrullinated histones, elastase, myeloperoxidase and MMP-3 ( 42 , 43 ). The release of neutrophil extracellular traps results in ineffective phagocytosis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive activation of neutrophils is known to decrease survival and enhance susceptibility to subsequent bacterial infections ( 41 ). One mechanism that may contribute to the pathology of sepsis is the release of neutrophil extracellular traps as they contain the beneficial antimicrobial nuclear proteins but also damaging citrullinated histones, elastase, myeloperoxidase and MMP-3 ( 42 , 43 ). The release of neutrophil extracellular traps results in ineffective phagocytosis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The release of NETs has been associated with tissue damage in several immune-mediated diseases, including chronic obstructive pulmonary disease, rheumatoid arthritis, and sepsis (Dicker et al, 2018;Khandpur et al, 2013;Colón et al, 2019). NETs cause tissue damage by extracellular exposure of DNA, granular proteins such as MPO, and histone, inducing apoptosis and fibrosis processes (Thammavongsa et al, 2013;Yadav et al, 2019).…”
Section: Sars-cov-2-activated Neutrophils Induce Lung Epithelial Cellmentioning
confidence: 99%
“…The DNA bound to MPO was quantified using the Quant-iT PicoGreen kit (Invitrogen; cat. P11496), as described (Colón et al, 2019;Czaikoski et al, 2016).…”
Section: Quantification Of Netsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cfDNA triggers the contact-pathway 13 and fixes complement 14 , MPO induces oxidative tissue damage 15 , NE cleaves tissue factor pathway inhibitor (TFPI) promoting thrombosis 16 , while histones cause platelet activation 17 and are directly toxic to endothelial cells 18 . In septic patients, plasma levels of NDPs correlate with end-organ damage and mortality 19,20 . It has been suggested that preventing NET release (NETosis) might be beneficial 21 , but we believe that this strategy may be ineffective as septic patients likely have a large amount of NETs released by the time they become clinically ill.…”
Section: Introductionmentioning
confidence: 99%